Information technologies in the implementation of Language education in a non-linguistic University - Anna L. Morozova; Tat’yana A. Kostyukova; Dzhamilya Kh. Godina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The possibilities of using information technologies in the implementation of language education in a non-linguistic University in the conditions of full transition to distance education due to the COVID-19 pandemic are revealed. Language education is recognized as a synthesis of learning and education in the interests of the individual, society and the state. However, the relevant section studying the implementation of online language education has not yet been properly developed in pedagogical science, so we are taking a step in an attempt to systematize the accumulated experience. Based on the analysis of domestic and foreign scientific sources and accumulated pedagogical experience, the effectiveness of online pedagogy is investigated. The research material includes: educational websites, educational platforms of MGIMO and Plekhanov Russian University of Economics, free applications (Google classroom, etc.) and platforms (Moodle, Edmodo.com etc.) in the implementation of the base of distance education in a foreign language. The study analyzes the practice of effective use of online pedagogy in the context of the implementation Of the Ministrys order No. 398, using the example of teaching a foreign language at the Moscow state Institute of international relations University) Ministry of foreign Affairs of the Russian Federation Odintsovo branch (Moscow region, Russia) and Plekhanov Russian University of Economics (Moscow) in March-July 2020. To achieve the goal of language learning under the COVID-19 quarantine, ICTs were used in four areas: educational platforms, online conferences, educational sites and applications for free language learning, and sites (with duplicate applications) for creating tests. Educational platforms Moodle, Edmodo, Google classroom, etc., allow teachers to create and conduct remote classes in off-line mode and have a rich educational potential for learning the language. The positive impact of distance learning on the final certification was recorded. The use of information provided on Internet resources can be effective in the implementation of language education, and the material posted on the sites can be selected taking into account the direction of training and adapted to a variety of innovative teaching methods and current needs of students. it is important now to focus on the search for a new didactics the didactics of mixed learning, the development of a new model of shifting emphasis: from focusing on your own content to public types of content; from reproductive methods of learning to active ones; from final assessment to formative; new formats of educational interaction horizontal /joint/mutual learning (peer-to-peer), etc. You should also create a new model of competencies of the teachers to work in the paradigm of online student -oriented pedagogy, which requires an understanding of the role of learning environment as Navigator training, ownership integration technologies full-time and e-media, external resources and systems of learning (MOOCS, adaptive systems, external platforms) and build on these foundations training route.